COVID-19, Domestic tourism and Indigenous Knowledge Systems in Zimbabwe - Ngoni Courage Shereni; Regis Musavengane; Erisher Woyo (Studia Periegetica)
This study aims to determine the role of indigenous knowledge systems (IKS) in rejuvenating domestic tourism in the context of suppressed international tourism demand. The current study is premised on the thinking that COVID-19 has changed the way countries do tourism and domestic tourism is now recognised for its ability to help the recovery of the tourism industry post-COVID-19. The infusion of IKS in tourism strategies is seen as important in encouraging locals to visit destinations within their countries. The study is based on a review of the literature on the nexus between indigenous knowledge systems, domestic tourism and COVID-19. The study contributes to the existing literature on domestic tourism by suggesting possible solutions to the industry based on IKS. In light of recent COVID-19 events in the tourism industry at large, it is becoming extremely difficult to ignore the importance of domestic markets.